Postresuscitative Effects of Mexidole on Myocardial Lipid Composition and Perioxidation - N. N. Andreyeva; I. V. Mukhina; T. I. Solovyeva (Общая реаниматология, 2005)
An experimental model of clinical death followed by reperfusion was used to study the postresuscitative effects of the anti-hypoxant mexidole on lipid composition and peroxidation rates in the rat myocardium. The use of mexidole in early reperfusion was shown to lead to the altered phospholipid composition of cardiomyocytes, the normalization of the activities of superoxide dismutase and catalase, the lower levels of malonic dialdehyde on postresuscitative day 30. Modifications of the myocardium lipid spectrum appeared as the elevated levels of phosphatidylserine and phosphatidylethanolamine that maintained intracellular ionic homeostasis and myocardial performance, as well as decreases in lysophosphatidylcholine having proarrhythmic activity and in sphingomyelin and phosphatidic acids.